2014
DOI: 10.1155/2014/837365
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Glycogene Expression in Different Mouse Tissues Using RNA-Seq Data

Abstract: Glycogenes regulate a wide array of biological processes in the development of organisms as well as different diseases such as cancer, primary open-angle glaucoma, and renal dysfunction. The objective of this study was to explore the role of differentially expressed glycogenes (DEGGs) in three major tissues such as brain, muscle, and liver using mouse RNA-seq data, and we identified 579, 501, and 442 DEGGs for brain versus liver (BvL579), brain versus muscle (BvM501), and liver versus muscle (LvM442) groups. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…This study picked multiple microarray datasets of MS, preprocessed and analyzed via R. Then the consensus data were utilized for different networks using Cytoscape and various other sources [ 21 - 23 ]. Gene-gene interactions have been discussed in one of the other studies [ 79 ] via GeneMANIA where comparative analysis of Glycogene expression was focused in different tissues. This study also discussed the identification of Hub node based on degree centrality via Cytoscape plugin.…”
Section: Discussionmentioning
confidence: 99%
“…This study picked multiple microarray datasets of MS, preprocessed and analyzed via R. Then the consensus data were utilized for different networks using Cytoscape and various other sources [ 21 - 23 ]. Gene-gene interactions have been discussed in one of the other studies [ 79 ] via GeneMANIA where comparative analysis of Glycogene expression was focused in different tissues. This study also discussed the identification of Hub node based on degree centrality via Cytoscape plugin.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the structure and function of biological networks is crucial for the exploration of biological phenomena. The interest in exploiting the use of network based studies to address key biological issues is ever increasing [ 52 54 ]. In this work, four functional modules or clusters were identified in Network 3 using the GLay plugin for Cytoscape.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of brain genes notes this limitation and discuses the need to extend the gene pool that is evaluated in a brain-wise approach [66,67]. Some bottom-up studies of GRNs across different tissues and diseases have shown how distributed modulation across a wide range of genes plays essential roles in function and pathophysiology [68][69][70][71]. Here we present a bottom-up model [34] that explores the molecular assemblies (in terms of gene expression) and the gene communities as the dynamic clusters that constitute functional regulatory units, as a first step to understand gene regulatory networks as the precursors of a brain archetype.…”
Section: Gene-wise Analysismentioning
confidence: 99%